KARAKTERISTIK MUTU VELVA PEPAYA DAN PISANG AMBON - Netti Herawati; Syawatul Mutiara; Emma Riftyan (Fakultas Pertanian Universitas Riau, 2024)
Frozen combination of fruit puree, sugar, and stabilizers is commonly used to produce velva, a frozen food product with a smooth texture similar to ice cream. Papaya fruit has a distinctive aroma, so if it is processed into processed velva products it will produce an aroma that is less favorable. The aroma of velva papaya can be improved by combining other fruits such as ambon banana which has a distinctive aroma. This research aimed to obtain the best ratio of papaya puree and ambon banana puree based on the quality characteristics of velva. This research used a completely randomized design (CRD) to produce 15 experimental units, with five treatments and three replications. The treatment in this study was PP1 (70:30), PP2 (60:40), PP3 (50:50), PP4 (40:60), and PP5 (30:70). Parameters observed include total solids, overrun, melting time, crude fiber content, vitamin C, and sensory evaluation. The variance results showed that overrun, melting time, crude fiber content, total solids, and sensory evaluation were significantly influenced by variations in the amount of papaya puree and ambon banana puree. Based on analysis parameters, the selected treatment was a ratio of papaya puree and ambon banana puree PP3 (50:50), producing a total solids of 27.75%, an overrun of 7.69%, a melting time of 14.15 minutes. The crude fiber content of 2.40%. vitamin C 23,47 mg. Orange in color, banana flavor, and soft and hedonically liked by the panelists.